Notes on the bionomy of two spider wasp species in an urban forest fragment in Brazil - Diego Marinho; Felipe Vivallo (Papéis Avulsos de Zoologia, 2020)
Abstract There are few studies dedicated to the natural history of Neotropical spider wasps (Pompilidae). When it comes to urban areas, the knowledge on these wasps is even scarcer. This study sheds light on the natural history of Auplopus cf. rufipes and A. cf. brasiliensis (Hymenoptera: Pompilidae: Ageniellini) from an urban Atlantic Forest fragment in the Jardim Botânico do Rio de Janeiro, Rio de Janeiro City, Brazil. Auplopus cf. rufipes displays a multivoltine pattern and frequently nests in bamboo canes scattered in the open areas, whereas A. cf. brasiliensis is a rare sight, with only a single nest collected from a hose trap-nest. Females of the former species show aggressive behaviour, which suggests a solitary lifestyle. Their nests were partly enveloped in a complex structure, similar to other species that build free-standing, unconcealed nests and display some degree of sociality. Such behaviour could not be observed for A. cf. brasiliensis. Despite that, nests of both species were built using mud pellets, though the brood cells differed regarding arrangement and position in the trap. Two parasites were found attacking the cells: Caenochrysis crotonis (Chrysididae) in a cell of A. cf. rufipes, and Chaenotetrastichus neotropicalis (Eulophidae) in two cells of A. cf. brasiliensis, both recorded for the first time. Auplopus cf. rufipes was found to prey on Frigga cf. quintensis (Salticidae), the first record of this genus as a host of Auplopus.